Pengaruh Pemasaran Digital dan Ulasan Pelanggan Online terhadap Keputusan Pembelian pada Pengguna Tokopedia di Kabupaten Nganjuk - Rifka Chintya Ade Gousmau; Indrian Supheni; Prasetya Tri Mahendra (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
This study aims to determine the influence of Digital Marketing and Online Customer Reviews on Purchase Decisions among Tokopedia users in Nganjuk Regency. The independent variables in this research are Digital Marketing (X₁) and Online Customer Reviews (X₂), while the dependent variable is Purchase Decision (Y). The method used is quantitative research with an associative approach. Data were collected through questionnaires distributed to 400 respondents who are Tokopedia users in Nganjuk Regency. The results show that partially, Digital Marketing (X₁) has a significant effect on Purchase Decisions with a significance value of 0.005, and Online Customer Reviews (X₂) also have a significant effect with a significance value of 0.000. Simultaneously, Digital Marketing and Online Customer Reviews have a significant effect on Purchase Decisions with a significance value of 0.000 and an F-count value of 69.653. Thus, an effective digital marketing strategy and positive customer reviews are important factors that sellers on Tokopedia should pay attention to in order to increase consumers' purchase decisions.